(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents the analytical scientific issues of further development of small business and private entrepreneurship in our Republic with the help of innovations, increasing the share of private entrepreneurship in the economy, positive acceleration of structural changes.